Asesmen Diagnostik Pendidikan Pancasila dalam Pembelajaran Berdiferensiasi pada Siswa Kelas IV SDN 64 Bengkulu Tengah - Susanti, Atika (Jurnal PGSD, 2025)
Understanding students' knowledge profiles is crucial for teachers to group them based on their respective abilities. Currently, there is a lack of understanding among teachers regarding students' initial abilities in comprehending the taught material. Consequently, some students have not fully mastered the material when given questions by the teacher. To address this issue, it is important for teachers to conduct diagnostic assessments to evaluate students' initial abilities regarding the material to be taught. This study aims to analyze the results of diagnostic assessments in the Pancasila Education subject as the foundation for implementing differentiated learning for fourth-grade students at SDN 64 Bengkulu Tengah. The research method used is descriptive quantitative. The quantitative approach is employed to analyze the data obtained from students' diagnostic assessments, while the qualitative approach is used to explore more in-depth information. The analysis results indicate that diagnostic assessments in civic education provide a comprehensive overview of students' needs and abilities that can be used as a guide in designing learning tailored to individual needs. Most fourth-grade students are at the developing stage rather than proficient, indicating a relatively low level of readiness for learning. The diagnostic assessment conducted through statement questions aimed to determine students' initial abilities. However, based on the assessment results, it appears that students have not fully understood the material to be taught.